Jelovo-bukovi gozdovi v zgornji Baški dolini (Julijske Alpe, zahodna Slovenija) - Dakskobler, Igor (Hacquetia, 2016)
Applying the standard Central-European method (Braun-Blanquet 1964) we phytosociologically researched the fir-beech stands in the upper Bača Valley (western Slovenia). After comparing their floristic composition with similar stands elsewhere in the Southeastern Alps and in the northern part of the Dinaric mountains we classified them into a new geographical variant Homogyno sylvestris-Fagetum Marinček et al. 1993 var. geogr. Scopolia carniolica var. geogr. nova. We established four site subunits, subassociations -clematidetosum alpinae, -typicum (= adenostyletosum glabrae) and -stellarietosum montanae as well as an edaphic variant with the species Luzula luzuloides, which indicates a transition (or connection) with the stands of the syntaxon Luzulo-Fagetum Meusel 1937 var. geogr. Cardamine trifolia (Marinček 1983) Marinček & Zupančič 1995 abietetosum (Marinček & Dakskobler 1988) Marinček & Zupančič 1995.